The Arabic Language from Its Earliest Times to the Age of Ignorance - Omar Adeeb Shaker Jnaidi (Şarkiyat Mecmuası)
The study of the history of the beginnings of the Arabic language is shrouded in complete darkness, as nothing is known about its infancy or when it began. It is only known to have been mature and complete in the literature of the Jahiliyyah (pre-Islamic era known as the Age of Ignorance). Arabic indubitably went through various stages before reaching that level of maturity. In this respect, does any possibility exist for examining its ancient history or knowing when it arose, what stages it went through, and whether a relationship exists between it and the Semitic languages. Many consider answering these questions and providing accurate judgments about them to be difficult, due to the ambiguousness of Arabic’s infancy, the few available sources about that era that thus provide no clear picture, and the lack of scholars finding any engraved or written traces that might shed light on its initial condition. The main aim of this research will attempt to identify the early historical stages of the Arabic language. Along the way, the study will first touch upon the disagreements among ancient Arab linguists regarding Arabic’s first inception and who were the first to speak it, their belief in its antiquity, their assumptions about its development, and their realization of its linguistic historical kinship with the Semitic languages. The study will then move on to the modernists among the Orientalists and Arab linguists regarding their attempt to reveal the beginnings of Arabic by relying on comparative studies and readings of ancient inscriptions. The study will also take a look at their views on the relationship between Arabic and Semitic, with the research finally ending by listing their perceptions about Arabic’s infancy and the stages it went through early on in its inception.